2008
DOI: 10.1038/nsmb.1414
|View full text |Cite
|
Sign up to set email alerts
|

DNA apurinic-apyrimidinic site binding and excision by endonuclease IV

Abstract: Escherichia coli endonuclease IV is an archetype for an abasic or apurinic-apyrimidinic endonuclease superfamily crucial for DNA base excision repair. Here biochemical, mutational and crystallographic characterizations reveal a three-metal ion mechanism for damage binding and incision. The 1.10-A resolution DNA-free and the 2.45-A resolution DNA-substrate complex structures capture substrate stabilization by Arg37 and reveal a distorted Zn3-ligand arrangement that reverts, after catalysis, to an ideal geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 49 publications
4
133
1
Order By: Relevance
“…It should be noted that UVDE also recognizes AP sites, platinum G -G diadducts, uracil, dihydrouracil, and other oxidative DNA-damage products and introduces a nick immediately 5 0 to the lesions (Avery et al 1999;Kanno et al 1999). A crystal structure of UVDE derived from the thermophilic bacterium Thermus thermophilus was solved (Paspaleva et al 2007) and showed essential structural features of a TIM-barrel fold shared with that of Endo IV (Hosfield et al 1999;Garcin et al 2008). Although both enzymes share some characteristic features of a DNA-binding groove, where both the damaged bases and their opposite bases are thought to flip out of the double helix into the binding groove, the predicted residues in the structure of UVDE make a larger space for the flipped-out UV lesions than in Endo IV.…”
Section: Structural Biology Of Uvdementioning
confidence: 99%
“…It should be noted that UVDE also recognizes AP sites, platinum G -G diadducts, uracil, dihydrouracil, and other oxidative DNA-damage products and introduces a nick immediately 5 0 to the lesions (Avery et al 1999;Kanno et al 1999). A crystal structure of UVDE derived from the thermophilic bacterium Thermus thermophilus was solved (Paspaleva et al 2007) and showed essential structural features of a TIM-barrel fold shared with that of Endo IV (Hosfield et al 1999;Garcin et al 2008). Although both enzymes share some characteristic features of a DNA-binding groove, where both the damaged bases and their opposite bases are thought to flip out of the double helix into the binding groove, the predicted residues in the structure of UVDE make a larger space for the flipped-out UV lesions than in Endo IV.…”
Section: Structural Biology Of Uvdementioning
confidence: 99%
“…The data were qualified as '2' (,5 %), '+/2' (5-10 %), '+' (10-50 %), '++' (50-80 %) and '+++' (.80 %). The Nfo Eco counterparts of the targeted amino acid residues were found to interact with no, one or two of the three divalent cations (Zn 1 , Zn 2 and Zn 3 ) that were identified previously in Nfo Eco 's active site (Garcin et al, 2008;Hosfield et al, 1999 In addition to the damage-specific endoncleolytic activities of Nfo Mpn and Nfo Mge , we also found these proteins to possess non-specific 39A59 exonucleolytic activity. Such activity has previously also been attributed to other Nfo proteins (Back et al, 2006;Kerins et al, 2003;Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 64%
“…Both Mg 2+ and Mn 2+ , however, did stimulate the proteins' activities. Similarly, the wild-type Nfo Eco protein was stimulated by Mn 2+ , indicating that this cation may be favoured over Zn 2+ at one of the three 'Zn 2+ ' sites (Garcin et al, 2008); on the basis of crystallographic and biochemical analyses, it is likely that this is the Zn 3 site (Garcin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations